Serotype and multilocus sequence typing of Streptococcus suis from diseased pigs in Taiwan - Wu, Ching-Fen; Chen, Siou-Hui; Chou, Chi-Chung; Wang, Chao-Min; Huang, Szu-Wei; Kuo, Hung-Chih (Scientific reports, 2023)
Streptococcus suis ( S. suis ) infection can cause clinically severe meningitis, arthritis, pneumonia and septicemia in pigs. To date, studies on the serotypes, genotypes and antimicrobial susceptibility of S. suis in affected pigs in Taiwan are rare. In this study, we comprehensively characterized 388 S. suis isolates from 355 diseased pigs in Taiwan. The most prevalent serotypes of S. suis were serotypes 3, 7 and 8. Multilocus sequence typing (MLST) revealed 22 novel sequence types (STs) including ST1831-1852 and one new clonal complex (CC), CC1832. The identified genotypes mainly belonged to ST27, ST94 and ST1831, and CC27 and CC1832 were the main clusters. These clinical isolates were highly susceptible to ceftiofur, cefazolin, trimethoprim/sulfamethoxazole and gentamicin. The bacteria were prone to be isolated from cerebrospinal fluid and synovial fluid in suckling pigs with the majority belonging to serotype 1 and ST1. In contrast, ST28 strains that corresponded to serotypes 2 and 1/2 were more likely to exist in the lungs of growing-finishing pigs, which posted a higher risk for food safety and public health. This study provided the genetic characterization, serotyping and the most current epidemiological features of S. suis in Taiwan, which should afford a better preventative and treatment strategy of S. suis infection in pigs of different production stages.